173k views
0 votes
Proof by mathematical induction

Proof by mathematical induction-example-1
User Bussller
by
5.4k points

1 Answer

4 votes

Answer:

See below.

Explanation:

I will assume that 3n is the last term.

First let n = k, then:

Sum ( k terms) = 7k^2 + 3k

Now, the sum of k+1 terms = 7k^2 + 3k + (k+1) th term

= 7k^2 + 3k + 14(k + 1) - 4

= 7k^2 + 17k + 10

Now 7(k + 1)^2 = 7k^2 +14 k + 7 so

7k^2 + 17k + 10

= 7(k + 1)^2 + 3k + 3

= 7(k + 1)^2 + 3(k + 1)

Which is the formula for the Sum of k terms with the k replaced by k + 1.

Therefore we can say if the sum formula is true for k terms then it is also true for (k + 1) terms.

But the formula is true for 1 term because 7(1)^2 + 3(1) = 10 .

So it must also be true for all subsequent( 2,3 etc) terms.

This completes the proof.

User Arlin
by
6.3k points